Peningkatan Repurchase Intention Melalui Product Quality dan OCR Serta Brand Trust sebagai Variabel Intervening - Azizah, Nur; Nurhayati, Tatiek; Ratnawati, Alifah (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to determine the effect of Online Customer Review and Product Quality in increasing Repurchase Intention through Brand Trust. The sampling technique used in this study was purposive sampling. With the criteria of students in Semarang, aged > 17 years, have used Avoskin skincare products, have repurchased Avoskin skincare products at least twice on e-commerce, consumers who have seen online reviews of Avoskin products on e-commerce. Using a quantitative approach with 200 respondents, data collection techniques through questionnaires distributed online. Testing in this study used Structural Equation Modeling-Partial Less Square (SEM PLS). The results of this study indicate that Online Customer Review and Product Quality have an effect on Brand Trust and Repurchase Intention. In addition, Brand Trust also plays an important mediator in the relationship between Online Customer Review and Product Quality and Repurchase Intention.